AN IMPROVED SIDE VIEW FACE AUTHENTICATION USING WAVELETS AND NEURAL NETWORKS (International Journal of Engineering Sciences & Management Research, 2014)
This paper proposes a side-view face authentication method based on Discrete Wavelet Transform (DWT) and Neural Networks.A subset selection method that increases the number of training samples and permits subsets to preserve the global information ispresented. The authentication method can be summarized to have the following steps: profile extraction, wavelet decomposition,subset splitting and Neural Network verification. This method takes the advantage of wavelet’s localization property in bothfrequency and spatial domains, while maintaining the generalized properties of Neural Network.